Pattern of dermatoses in tertiary care hospital at Sahiwal, Pakistan (Journal of Fatima Jinnah Medical University, 2019)
Background: This study was carried out to assess the pattern of various dermatoses which will help in recognition of preventive measures to reduce their number in a tertiary care hospital.Patients and methods: An observational study was conducted on patients, irrespective of age and gender, who attended the Dermatology Department DHQ Teaching Hospital Sahiwal/Sahiwal Medical College from Jan 2017 to June 2017. Patients were diagnosed clinically on the basis of history and clinical examination. Laboratory investigations and skin biopsies were performed in doubtful cases.Results: A total of 6367 patients presented in the outpatient department of Dermatology, DHQ Teaching Hospital Sahiwal, Pakistan. Out of these 3322 (52%) were females and 3045 (48%) were males. The majority (62.8%) of patients were in the 14–49 years age group. Infestations (scabies) and cutaneous infections were the most common skin conditions in 2845 (44.7%) patients followed by eczema in 1301 (20.4%). A large number of patients including 753 (11.8%) were reported with fungal infections as compared to 250 (3.9%) with bacterial and 223 (3.5%) with viral infections.  Acne was observed in 725 (11.4%) patients, urticaria in 370 (5.8%) patients, pigmentary dermatoses in 314 (4.9%) patients, papulosquamous disorders in 255 (4.0%) patients and xerosis in 191 (2.9%) patients. Rest of patients belonged to miscellaneous dermatoses 296 (4.6%) and hair diseases 70 (1.0%).Conclusion: Major burden of skin diseases especially scabies and infections in tertiary care health facilities need to be curtailed by improving primary healthcare in developing countries.
Keywords: Dermatoses; Scabies; Eczema